(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is devoted to the field of phraseology, which should be one of the lexicology, in which phraseological units in German and Uzbek linguistics are classified. Analyzing the views of linguists. They are given general conclusions